2020
DOI: 10.1002/jia2.25488
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of discrimination and internalized stigma compromise retention in HIV care among adolescents: findings from a South African cohort

Abstract: Introduction Efficacious antiretroviral treatment (ART) enables people to live long and healthy lives with HIV but young people are dying from AIDS‐related causes more than ever before. Qualitative evidence suggest that various forms of HIV‐related discrimination and resulting shame act as profound barriers to young people’s engagement with HIV services. However, the impact of these risks on adolescent retention in HIV care has not been quantified. This study has two aims: (1) to examine whether and how differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 42 publications
7
51
0
3
Order By: Relevance
“…In Zimbabwe, retention in care improved significantly between 2010 and 2015 except for patients in their first six months 10 . Beyond the impact on individual morbidity and mortality, early losses from care are associated with internalized stigma, leading to social isolation, fear of disclosure, and discrimination, which potentially compound the inherent challenges in returning to care 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In Zimbabwe, retention in care improved significantly between 2010 and 2015 except for patients in their first six months 10 . Beyond the impact on individual morbidity and mortality, early losses from care are associated with internalized stigma, leading to social isolation, fear of disclosure, and discrimination, which potentially compound the inherent challenges in returning to care 11 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches hold out hope, but the challenges are great. For example, in one recent a cohort study of approximately 1,000 adolescents in South Africa, retention on ART was only 38% (Pantelic, Casale, Cluver, Toska, & Moshabela, 2020). In a systematic review of interventions to improve adolescent ART adherence few interventions were found to be effective (Reif et al, 2020).…”
Section: Treatment Issues Concerning Children Living With Hivmentioning
confidence: 99%
“…Moreover, individuals with travel experience in the epicenter were affected by internalized stigma [ 23 ], and that could be psychologically damaging for individuals affected by COVID-19, since high levels of internalized stigma might be associated with lower levels of self-esteem and increased depression [ 10 , 24 ]. In addition, previous studies have shown the association between multifaceted discrimination and retention cares in HIV-positive young adolescents; this process was mediated by internalized stigma [ 25 ]. Although the repercussion of internalized stigma has been widely revealed, the psychological process was still unclear in the context of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning infectious disease-perceived discrimination, individuals may exhibit feelings of shame and stigmatization synchronously. Moreover, shame has been shown to mediate the negative mental and physical health consequences of stigmatization, both shame and stigma are directly related to mental health problems [ 25 , 28 , 29 ]. However, they probably have different manifestations.…”
Section: Introductionmentioning
confidence: 99%